Pathogenesis and novel therapeutics of regulatory T cell subsets and interleukin-2 therapy in systemic lupus erythematosus - Tsai, Yi-Giien; Liao, Pei-Fen; Hsiao, Kai-Hung; Wu, Hung-Ming; Lin, Ching-Yuang; Yang, Kuender D. (Frontiers in Immunology, 2023)
Systemic lupus erythematosus (SLE) is a heterogeneous multisystem inflammatory disease with wide variability in clinical manifestations. Natural arising CD4+ regulatory T cells (Tregs) play a critical role in maintaining peripheral tolerance by suppressing inflammation and preventing autoimmune responses in SLE. Additionally, CD8+ regulatory T cells, type 1 regulatory T cells (Tr1), and B regulatory cells also have a less well-defined role in the pathogenesis of SLE. Elucidation of the roles of various Treg subsets dedicated to immune homeostasis will provide a novel therapeutic approach that governs immune tolerance for the remission of active lupus. Diminished interleukin (IL)-2 production is associated with a depleted Treg cell population, and its reversibility by IL-2 therapy provides important reasons for the treatment of lupus. This review focuses on the pathogenesis and new therapeutics of human Treg subsets and low-dose IL-2 therapy in clinical benefits with SLE.